Ipsilateral common iliac artery plus femoral artery clamping for inducing sciatic nerve ischemia/reperfusion injury in rats: a reliable and simple method - Nouri, Mohsen; Rahimian, Reza; Fakhfouri, Gohar; Rasouli, Mohammad R; Mohammadi-Rick, Sanaz; Barzegar-Fallah, Anita; Asadi-Amoli, Fahimeh; Dehpour, Ahmad Reza (Journal of Brachial Plexus and Peripheral Nerve Injury, 2008)
The aim of this study was to develop a practical model of sciatic ischemia reperfusion (I/R) injury producing serious neurologic deficits and being technically feasible compared with the current time consuming or ineffective models. Thirty rats were divided into 6 groups (n = 5). Animal were anesthetized by using ketamine (50 mg/kg) and xylazine (4 mg/kg). Experimental groups included a sham-operated group and five I/R groups with different reperfusion time intervals (0 h, 3 h, 1 d, 4 d, 7 d). In I/R groups, the right common iliac artery and the right femoral artery were clamped for 3 hrs. Sham-operated animals underwent only laparotomy without induction of ischemia. Just before euthanasia, behavioral scores (based on gait, grasp, paw position, and pinch sensitivity) were obtained and then sciatic nerves were removed for light-microscopy studies (for ischemic fiber degeneration (IFD) and edema). Behavioral score deteriorated among the ischemic groups compared with the control group (p < 0.01), with maximal behavioral deficit occurring at 4 days of reperfusion. Axonal swelling and IFD were found to happen only after 4 and 7 days, respectively. Our observations led to an easy-to-use but strong enough method for inducing and studying I/R injury in peripheral nerves.